Study of Meda Dhatu With Special Reference to Obesity - YADAV, SUMAN; KUMAR, SUNIL (International Research Journal of Ayurveda & Yoga, 2020)
Basically, obesity is a lifestyle disorder and also most common nutritional disorders, defined as excess body weight and fat that possess health risk. In the present days Sthaulya or obesity is a very important disease, which is increasing very rapidly in the world. Meda acts as the main Dushya in Sthaulya which has an immense importance. Sneha Dhatu which has quite similarities to the concentrated Ghrita termed as Meda, which has been practically seen in the fat deposition sites like as subcutaneous tissue, superficial fascia and omentum. Any derangement of the normal pathophysiology of the Meda Dhatu leads to several disorders, obesity is one of them. The distribution and role of Meda in Sthaulya is the same as the adipose tissue in obesity. However, in modern medical science, any effective medicine is not found till today, so Ayurveda can help in this condition by its holistic approach and by maintaining the Meda Dhatu in a balanced state. It is obligatory to understand its roots, prior to the treatment of this disorder.